2019
DOI: 10.1002/ejlt.201900333
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Sophorolipids and Nisin and Their Combination against Foodborne Pathogen Staphylococcus aureus

Abstract: In food processing, both preservatives and surfactants are usually added to ensure the quality of food. Sophorolipids (SLs) are extracellular biosurfactants produced by yeasts that have antibacterial activities. Nisin is a polycyclic antibacterial peptide produced by Lactococcus lactis. In this study, the possibility of using SLs alone as a preservative and in combination with nisin as a compound additive is investigated. SLs and nisin exhibit effective antibacterial activities against foodborne pathogen Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(49 reference statements)
2
8
0
Order By: Relevance
“…Production of sophorolipids from marine yeast Rhodotorula rubra has been observed to show antibacterial activities against foodborne pathogens E. coli and S. aureus with the utilization of Macrocystis pyrifera extract as a nutrient source [ 68 ]. Similar antibacterial potentials were demonstrated by Chen et al when they combined nisin with sophorolipids to form antimicrobial food preservatives [ 69 ]. Based on Gaur et al [ 70 ], sophorolipids from Candida albicans and Candida glabrata have been shown to be effective antibacterial biomolecules against both Gram-positive and Gram-negative bacterial pathogens through the formation of reactive oxygen species (ROS) [ 70 ].…”
Section: Applications Of Sophorolipids In Food and Healthsupporting
confidence: 75%
“…Production of sophorolipids from marine yeast Rhodotorula rubra has been observed to show antibacterial activities against foodborne pathogens E. coli and S. aureus with the utilization of Macrocystis pyrifera extract as a nutrient source [ 68 ]. Similar antibacterial potentials were demonstrated by Chen et al when they combined nisin with sophorolipids to form antimicrobial food preservatives [ 69 ]. Based on Gaur et al [ 70 ], sophorolipids from Candida albicans and Candida glabrata have been shown to be effective antibacterial biomolecules against both Gram-positive and Gram-negative bacterial pathogens through the formation of reactive oxygen species (ROS) [ 70 ].…”
Section: Applications Of Sophorolipids In Food and Healthsupporting
confidence: 75%
“…Naturally produced fatty acid monoglycerides have bacteriostasis to S. aureus , B. subtilis , Pseudomonas aeruginosa , and E. coli 16 . Chen et al 17 . found that the combined application of sophora lipids and streptococcus has a strong bacteriostasis on food‐borne S. aureus .…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcal food contamination represents the greatest economically significant foodborne illness [ 28 ] and produces gastrointestinal illness through a wide variety of toxins [ 29 ], including staphylococcal enterotoxins characterized by vomiting and diarrhea within 2 to 6 h after the consumption of contaminated food [ 30 , 31 , 32 ]. A large number of daily consumed foods serve as an optimum growth medium for S. aureus [ 27 ], and this varies from country to country, especially due to different habits in food consumption [ 33 ].…”
Section: Introductionmentioning
confidence: 99%